Restless gossamers: antibody clearance by hydrodynamic flow forces generated at the surface of motile trypanosome parasites - Dean, SD; Matthews, KR (Cell Press, 2007)
Trypanosomes evade antibody-mediated lysis via antigenic variation and rapid antibody removal from their cell surface. Recently, in Cell, Engstler et al. (2007) have discovered the mechanism for antibody clearance. Hydrodynamic forces generated by trypanosome swimming create a current, causing surface-bound antibodies to act as “molecular sails.” Consequently, they are swept to the cell posterior, internalized via the flagellar-pocket, and degraded. Hydrodynamic sorting is a novel biological process, possibly applicable in other contexts.